2019
DOI: 10.4236/ijohns.2019.86023
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cancer Early Identification of Malnutrition High Risk Patients and Quality of Life Optimization

Abstract: Malnutrition in Head and neck cancer (HNC) patients can be present at the moment of diagnosis. The nutritional status is determinant for the treatment success and quality of life of the patients. The nutritional status gradually declines during treatment and the majority of patients undergoing treatment will need nutritional therapy. On the other hand, HNC, like other cancers, can induce a paraneoplastic syndrome that leads to cachexia. This cachexia status is most of the times the cause of death or the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Five main advantages related with cancer patients are consistently and actually presented in literature regarding PRO incorporation in daily clinical practice. They are: (1) stepped care models design reflecting patient’s disease pathway [ 4 , 5 , 31 , 32 , 34 , 36 – 57 ] (2) prognosis value [ 2 4 , 22 , 31 , 34 , 37 43 , 47 , 50 , 53 , 57 – 74 ] (3) communication improvements [ 4 , 5 , 10 , 22 , 31 , 32 , 34 , 36 , 38 , 40 43 , 46 50 , 53 , 55 , 65 69 , 71 82 ], (4) patient safety optimization [ 4 , 5 , 10 , 30 , 31 , 34 , 36 , 39 43 , 47 , 48 , 52 , 53 , 55 , 56 , 60 62 , 64 66 , 68 , 70 , 72 74 , 77 87 ] and (5) healthcare risk identification, i.e., unmet problems identification, symptom detection and symptom control [ 2 ,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Five main advantages related with cancer patients are consistently and actually presented in literature regarding PRO incorporation in daily clinical practice. They are: (1) stepped care models design reflecting patient’s disease pathway [ 4 , 5 , 31 , 32 , 34 , 36 – 57 ] (2) prognosis value [ 2 4 , 22 , 31 , 34 , 37 43 , 47 , 50 , 53 , 57 – 74 ] (3) communication improvements [ 4 , 5 , 10 , 22 , 31 , 32 , 34 , 36 , 38 , 40 43 , 46 50 , 53 , 55 , 65 69 , 71 82 ], (4) patient safety optimization [ 4 , 5 , 10 , 30 , 31 , 34 , 36 , 39 43 , 47 , 48 , 52 , 53 , 55 , 56 , 60 62 , 64 66 , 68 , 70 , 72 74 , 77 87 ] and (5) healthcare risk identification, i.e., unmet problems identification, symptom detection and symptom control [ 2 ,…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies reviewed the evidence that the communication processes in health systems are complex. PROs incorporation in oncology improves clinical practice [ 42 , 47 , 92 ], structures the communication, develops effective communication tools and communication skills training [ 93 95 ], and contributes to the delivery of effective oncology high-quality care [ 34 , 39 , 76 ], improved patient-safety and patient satisfaction, and reduces patient anxiety [ 39 , 42 , 48 , 49 , 65 67 , 77 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some social factors can also worsen the patient's nutritional status, including poor dietary habits at baseline, restrictions on dietary choices, lack of social support, depression, and high alcohol consumption [9]. Silva et al [11] reported that risk factors for malnutrition in patients with HNC included the tumor's location in the oral cavity and oropharynx, younger age, lower education status, and a BMI lower than 18.5 at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of head and neck cancer, BMI has been identified as a predictive factor for malnutrition at the time of diagnosis (Arribas et al, 2013 ). Furthermore, previous research has indicated that patients classified as being at high risk of malnutrition experience persistent and significantly impaired quality of life across various domains (Silva et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%